Organic Crop Production – Ambitions and Limitations
DOI: 10.1007/978-1-4020-9316-6_3
|View full text |Cite
|
Sign up to set email alerts
|

Can Organic Crop Production Feed the World?

Abstract: Agriculture provides the most essential service to mankind, as production of crops in sufficient amounts is necessary for food security and livelihood. This chapter examines the question of whether organic agriculture can produce enough food to meet future demand. This question relates to a moral imperative and any evaluation must therefore be based on objective scientific facts excluding ideological bias, political correctness, economic incentives or environmental opinions. The chapter begins by defining the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
1
3

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 98 publications
5
54
1
3
Order By: Relevance
“…In developing nations, they found a mean yield increase of 174.6% (with a 95% confidence interval of 156.0 to 191.2%) when diversified farming practices were employed, compared with resource-poor (generally subsistence) farming strategies (138 comparisons from 29 studies). These results were contested, however, by authors who suggested that organic management would produce similar yields only if off-farm sources of manure were utilized, or when utilizing leguminous noncrop rotations that would decrease overall yields over the full crop rotation cycle (Kirchmann et al 2008). Subsequently, two new studies (de Ponti et al 2012, Seufert et al 2012) critiqued the Badgley et al (2007) study, primarily based on the choice of studies included in the Badgley study.…”
Section: Resiliency To Environmental Disturbances: Severe Weather Conmentioning
confidence: 99%
“…In developing nations, they found a mean yield increase of 174.6% (with a 95% confidence interval of 156.0 to 191.2%) when diversified farming practices were employed, compared with resource-poor (generally subsistence) farming strategies (138 comparisons from 29 studies). These results were contested, however, by authors who suggested that organic management would produce similar yields only if off-farm sources of manure were utilized, or when utilizing leguminous noncrop rotations that would decrease overall yields over the full crop rotation cycle (Kirchmann et al 2008). Subsequently, two new studies (de Ponti et al 2012, Seufert et al 2012) critiqued the Badgley et al (2007) study, primarily based on the choice of studies included in the Badgley study.…”
Section: Resiliency To Environmental Disturbances: Severe Weather Conmentioning
confidence: 99%
“…Soil quality tends to improve under organic management based on measurements of soil organic matter [39,41], though no-till conventional agriculture measured highest of all in some studies [9]. Although organic yields typically lag behind conventional yields [42], in drought years the opposite has been shown, which is attributed to the higher water holding capacity of soils under organic management [43,44]. Overall, organic production uses less energy per production unit due to the high energy costs of conventional fertilizer and pesticides [39,44,45].…”
Section: The Rise Of Organic Farmingmentioning
confidence: 99%
“…However, it can be a challenge to grow the necessary biomass in the cover crop to provide effective weed control, and the technique may not be possible in water-limited environments due to water competition by the cover crop [37]. Perennial weeds pose a particular problem, as they are typically able to grow through the mulch [37,42,55].…”
Section: Challenges In Organic Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…Although these data clearly showed that organic management increased SOC, it is often criticized that increased SOC stocks originate from massive imports of organic matter taken from elsewhere (13,17,18). To examine the potential impact of imported organic matter, we analyzed a subset of studies representing organic farming systems with zero net input separately.…”
mentioning
confidence: 99%